Relationship between jumping performance and running economy in runners and soccer players - Wallner, D.; Simi, H.; Hutz, B.; Hofmann, P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Muscles, tendons and ligaments are able to store and then release energy during exercise (Anderson & Pandy, 1993) and can thus reduce energy cost of running (Alexander, 1991). The elastic abilities of the ankle joint (Achilles tendon and arch of the foot) are of special importance for increasing energy efficiency during running (Ker at al. 1987). The aim of the study was to analyse the relationship between jumping performance and running economy in runners and soccer players. Method: Male soccer players (N=11) and runners (N=9) were tested. Jumping performance was determined by means of a drop jump test (30 cm platform) and calculated based on the contact time and the following jump. The subjects tried to minimize duration of ground contact and maximize the height of the vertical jump (support of arm action). In order to analyse running economy, subjects performed an incremental exercise test on a motor-driven treadmill. Oxygen uptake (VO2) was measured continuously and blood lactate concentration (La) was measured at rest and after every load step (increments were 0.5 km/h every minute). Running economy was defined as the oxygen consumption at 11.7 and 14.9 km/h, which represents the mean running speed at the first (vLTP1) and the second (vLTP2) lactate turn point of both groups. Results: Mean VO2max was 55.3±3.5 ml/kg/min in runners and 54.4±3.5 ml/kg/min in soccer players with no significant differences between them (p>0.05). The mean running speed of soccer players and runners at LTP1 was 11.3±0.5 km/h and 12.3±0.7 km/h respectively, while at vLTP2 it was 14.3±0.7 and 15.6±0.6 km/h respectively. Significant differences were found between groups both at vLTP1 and vLTP2 (p<0.05). Mean drop jumping performance was 61.3±9.8 W/kg in runners and 62.0±10.3 W/kg in soccer players with no significant difference between the two groups (p>0.05). Jumping performance was significantly related to oxygen consumption in runners at 11.7 km/h (r2=0.648; p<0.01) and at 14.9 km/h (r2=0.699; p<0.01), but not in the soccer players (p>0.05). Discussion: The significant correlation found between jumping performance and oxygen consumption (running economy) in runners may be explained by their superior running technique compared to a more inhomogeneous technical ability in the soccer players. Only some of the soccer players were able to use the elastic properties of the ankle in the way that highly trained runners do. Conclusion: Drop jump performance is associated with running economy in technically educated runners. References: Alexander R. (1991) Energy-saving mechanisms in walking and running. J Exp Biol 160, 55-69 Anderson F.C., Pandy M.G. (1993) Storage and utilization of elastic strain energy during jump. J Biomechanics 26(12), 1413-1427 Ker R.F., Bennett M.B., Bibby S.R., Kester R.C., Alexander R. McN. (1987) The spring in the arch of the human foot. Nature 325 (7000), 147-149